Relative Target Setting and Cooperation - HOLZHACKER, MARTIN; KRAMER, STEPHAN; MATĚJKA, MICHAL; HOFFMEISTER, NICK (Journal of Accounting Research, 2019)
ABSTRACT A large stream of work on relative performance evaluation highlights the benefits of using information about peer performance in contracting. In contrast, the potential costs of discouraging cooperation among peers have received much less attention. The purpose of our study is to examine how the importance of cooperation affects the use of information about peer performance in target setting, also known as relative target setting. Specifically, we use data from an industrial services company where business unit managers need to share specialized equipment and staff with their peers to manage bottlenecks in their capacity. We construct several empirical proxies for the costs and benefits of information about peer performance and examine their effects on target setting. We find robust evidence that the sensitivity of target revisions to past peer performance is higher when peer group performance has greater capacity to filter out noise but lower when the importance of cooperation among peers is greater.